ISOLATION AND ACTIVITY ANTIOXIDANT TEST OF COCOA POD HUSK ETHYL ASETAT EXTRACTS (Theobroma cacao L) - Binawati Ginting; Ilham Maulana; Nurdin Saidi; Syarifah Yanti Astryna (Universitas Syiah Kuala, 2019)
Isolation and testing of antioxidant activity with1,1-difenil-2-pikril hidrazil (DPPH) from ethyl acetate extract ofcocoa pod husk(Theobroma cacao L) has been carried out.Theobroma cacaoextract (TCE) showed highly strong antioxidant activity with IC50 = 8,75 ppm and vitamine C = 6,07 ppm as positive control. Isolation of the active components of TCE by column chromatography using silica gel absorbent 60 mesh ASTM (Merck 774) and the eluent n-hexane: ethyl acetate (9:1), obtained 7 fraction combined (TCE 1 to TCE 7). There are 6 combined fractions having the potential as antioxidants, namely TCE 2 to TCE 7 with a range of IC50 (6,46 ppm – 91,8 ppm). TCE 2 fraction has a very strong antioxidant activity with IC50 = 6,46 ppm. Separation of TCE 2 fraction on silica column chromatography obtained 4 combined fractions (TCE 2.1 to TCE 2.4). The test results of antioxidant activity showed that TCE 2.4 had very strong activity with IC50 = 42,7 ppm.For the TCE 2.2 fraction, preparative TLC was carried out using eluent n-hexane: ethyl acetate (9.5: 0,5) obtained by TCE 2.2.4 isolate with a melting point of 114-120 °C and was a steroid class.